Prescription and Other Medication Use in Pregnancy. Issue 5 (May 2018) - Haas, David M.; Marsh, Derek J.; Dang, Danny T.; Parker, Corette B.; Wing, Deborah A.; Simhan, Hyagriv N.; Grobman, William A.; Mercer, Brian M.; Silver, Robert M.; Hoffman, Matthew K.; Parry, Samuel; Iams, Jay D.; et al.
Abstract : OBJECTIVE: To characterize prescription and other medication use in a geographically and ethnically diverse cohort of women in their first pregnancy. METHODS: In a prospective, longitudinal cohort study of nulliparous women followed through pregnancy from the first trimester, medication use was chronicled longitudinally throughout pregnancy. Structured questions and aids were used to capture all medications taken as well as reasons they were taken. Total counts of all medications taken including number in each category and class were captured. Additionally, reasons the medications were taken were recorded. Trends in medications taken across pregnancy and in the first trimester were determined. RESULTS: Of the 9, 546 study participants, 9, 272 (97.1%) women took at least one medication during pregnancy with 9, 139 (95.7%) taking a medication in the first trimester. Polypharmacy, defined as taking at least five medications, occurred in 2, 915 (30.5%) women. Excluding vitamins, supplements, and vaccines, 73.4% of women took a medication during pregnancy with 55.1% taking one in the first trimester. The categories of drugs taken in pregnancy and in the first trimester include the following: gastrointestinal or antiemetic agents (34.3%, 19.5%), antibiotics (25.5%, 12.6%), and analgesics (23.7%, 15.6%, which includes 3.6%; 1.4% taking an opioid pain medication). CONCLUSION: In this geographically and ethnically diverse cohort of nulliparous pregnant women, medication use was nearly universal and polypharmacy was common. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT01322529. Abstract : Nearly all pregnant women take at least one medication during pregnancy, with almost one third meeting the definition of polypharmacy.